Analysis of Mangrove Stress Levels Using the NDRE Index and SPAD Chlorophyll Sensor in the Air Telang Mangrove Reserve: Analisis Tingkat Stres Mangrove Menggunakan Pendekatan Indeks NDRE dan Sensor SPAD di Kawasan Hutan Lindung Air Telang - Efan Fatra Jaya; Muhammad Rendana; Febrian Hadinata (Journal of Global Sustainable Agriculture, 2025)
Monitoring mangrove health is essential for identifying stress caused by environmental and anthropogenic pressures, such as salinity, sedimentation, hydrological changes, and land clearing around the mangrove ecosystem. This study aims to map mangrove stress levels in the Air Telang Mangrove Reserve by integrating remote sensing data through the analysis of the NDRE (Normalized Difference Red Edge) index and SPAD (Soil Plant Analysis Development) measurements. A quantitative approach was applied using NDRE analysis from satellite imagery processed with ArcGIS and in-situ SPAD chlorophyll measurements. The NDRE analysis results indicate that mangrove vegetation is predominantly classified as healthy, covering an area of 2,300.61 ha (75.85%), with 2.29 ha (0.08%) categorized as very healthy, 639.14 ha (21.07%) under moderate stress, and 91.10 ha (3.00%) classified as highly stressed or non-vegetated. These findings suggest that the majority of mangroves are in good condition, while only a small portion has been detected as experiencing stress. The correlation between SPAD and NDRE values showed a strong positive relationship with a correlation coefficient of r = 0.748 (p < 0.001) and a coefficient of determination (R²) of 0.560. These results indicate that the NDRE index can represent chlorophyll content in mangrove vegetation and serve as an alternative to SPAD-based field measurements. Therefore, both SPAD measurements and NDRE vegetation indices can be considered effective tools for assessing the health or stress levels of mangrove ecosystems.